Combination Use of Tegafur and Apatinib as First-Line Therapy in Treatment of Advanced Gastric Cancer: A Single-Blinded Randomized Study - Chaofeng Li; Tao Tang; Wenyue Wang (Gastroenterology Research and Practice)
Objective. To investigate the efficacy and safety of the combination use of tegafur and apatinib as a first-line therapy strategy in advanced gastric cancer (GC). Methods. The present study included a total of 62 advanced GC patients. The patients were randomized into the combined group (treated with both tegafur and apatinib) and the control group (treated with only tegafur). Treatment efficacy, KPS score, nutrition condition, and progression-free survival time (PFS) were recorded. Results. Both the response and disease control rates were significantly higher in the combined group. The PFS time was remarkably higher and the KPS score was significantly reduced in the combined group after treatment. After treatment, both groups showed significantly increased nutrition risk, but the rates of patients with nutrition risk or innutrition were remarkably higher in the combined group. The ADR rates were also significantly higher in the combined group. Conclusion. The combination use could achieve good efficacy and prolong patients’ PFS time; however, apatinib also reduced the patients’ quality of life and enhanced the nutrition risk and adverse drug reactions.